STRATEGI PENGEMBANGAN PASAR DAN PENGUATAN PRODUK WISATA KAWASAN SOl,0-SELO-BOROHUDUR (SSB) - Rara Sugiarti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
The objectives of this research were 10 identify the problems related to developing tourism in Solo-Selo-Borobudur (SSB) region, particularly Cepogo-Selo-Sawangan (CSS) sub region, to identify the existing market. and to formulate strategies 10 develop the Solo- Selo-Borobudur market according to its product characteristics. This research was qualitative and descriptive in nature. Data consisted of primary and secondary Jata and were collected using interview. focus groupdiscussion(FGD) and site observation. Research results indicate that the problems of tourism development in Solo-Selo-Borobudur region are as follows: limited coordination among stakeholders, limited market distribution, limited tourism information service. limited product diversification, relatively low product quality, limited accessibility, limited professionalism. and relatively low commitment The existing tourism market for the SS8 region is mostly domestic and local visitors. Tourist motivations include adventure-based and relaxation. Their travel pattern was mostly with friends and relatives. The marketing strategies for SSU tourism products, particularly CSS sub region, include enhancing collaboration to market tourist products. organizing events, developing tourism information services, introducing product through familiarization trip, empowering travel agents, improving accessibility, increasing tourism product quality, strenghtening stakeholder commitment, improving human resources quality, and enhancing community participation.